A New Discovery of Carnivores Mammalian Skeleton Fossils of Late Miocene-Early Pliocene age from Chamchamal Area/Kurdistan Region/NE-Iraq - Fadhel, M. Ghafor; Kamal, A. Lawa; Karim, Kamal H. (Sulaimani Journal for Pure and Applied Sciences, 2003)
A new vertebrate skeleton of Late Miocene-Early Pliocene age has been discovered for the first time as concerning in Kurdistan, nearby Kanisard village (Chamchamal area, Kurdistan/NE-Iraq). The new vertebrate remains comprised of the skull, teeth, backbone, and legs of New Tethyian mammal, carnivorous type, recognized and collected within pebbly sandstone horizons of Mukdadyiah Formation. The mammalian skeleton bearing sequence is comprised of rhythmic alternations of reddish brown claystone and greenish grey pebbly sandstone, which is also characterised by megaripple marks, channel deposits, flute casts and clay balls, associated with the dominance of Skolithos and Scoyiena trace fossils. The terrestrial skeleton with bioturbation and the associated sedimentary structures indicates continental environment (fluvial depositional environments) mostly less than three meters deep. All conjugate lines of evidences, that is morphological criteria of skull, leg length and width, teeth types, size and numbers, Jaw curvatures outline and the overall vertebrate size and shape, specify that the carnivorous mammal is related to Canis family ( dog-like carnivorous). Its age when the individual is died estimated to be about 5 years, while its death possibly occurs before 8- 9 Million years ago. (That is Late Miocene).
Keywords: Carnivores Vertebrates; Mammalians fossil Mukdadyiah Formation Braided river deposits; terrestrial; Kurdistan; geology